Development of an E-book on Community Life Styles in the Preliterate Period Through Discovery Learning to Increase Historical Literacy in State Vocational School Students in Central Lampung Regency - Apriyani, Suci Ayu Putri; Sunardi, Sunardi; Pelu, Musa (Journal Corner of Education, Linguistics, and Literature, 2024)
In this research, the author summarizes the objectives of 1) Knowing the learning media needed to increase historical literacy among students at State Vocational Schools in Central Lampung Regency, 2) Knowing e-book learning media that are suitable for implementation in the learning process at State Vocational Schools in Central Lampung Regency, 3) determine the effectiveness of the E-Book learning media on the history of people's life patterns during the preliterate era through Discovery Learning to increase the historical literacy of State Vocational School students in Central Lampung Regency. Then the author researched using the R&D method by adapting the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The ADDIE development model adapted by Branch (2019) consists of five stages, namely analyze, design, develop, implement and evaluate. The increase in students' historical literacy can be measured using the N-Gain test which aims to determine the increase during the pre-test and post-test. The N-gain test results in the large group trial were 0.53 in the medium category. In the effectiveness testing process, experiments were carried out with pre-post tests on the experimental class. From the results of the experimental class, there was an increase in students' pre-post test scores. So the conclusion is that E-Books can be used and effectively increase students' historical literacy.